An animal model for Pierpont syndrome: a mouse bearing the Tbl1xr1Y446C/Y446C mutation. Issue 17 (13th April 2022) - Hu, Yalan; Lauffer, Peter; Stewart, Michelle; Codner, Gemma; Mayerl, Steffen; Heuer, Heike; Ng, Lily; Forrest, Douglas; van Trotsenburg, Paul; Jongejan, Aldo; Fliers, Eric; Hennekam, Raoul; et al.
Abstract: Pierpont syndrome is a rare disorder characterized mainly by global developmental delay, unusual facial features, altered fat distribution in the limbs and hearing loss. A specific mutation (p.Tyr446Cys) in TBL1XR1, encoding a WD40 repeat-containing protein, which is a component of the SMRT/NCoR (silencing mediator retinoid and thyroid hormone receptors/nuclear receptor corepressors), has been reported as the genetic cause of Pierpont syndrome. Here, we used CRISPR-cas9 technology to generate a mutant mouse with the Y446C mutation in Tbl1xr1, which is also present in Pierpont syndrome. Several aspects of the phenotype were studied in the mutant mice: growth, body composition, hearing, motor behavior, thyroid hormone state and lipid and glucose metabolism. The mutant mice ( Tbl1xr1 Y446C/Y446C ) displayed delayed growth, altered body composition with increased relative lean mass and impaired hearing. Expression of several genes involved in fatty acid metabolism differed in white adipose tissue, but not in liver or muscle of mutant mice compared to wild-type mice ( Tbl1xr1 +/+ ). No difference in thyroid hormone plasma concentrations was observed. Tbl1xr1 Y446C/Y446C mice can be used as a model for distinct features of Pierpont syndrome, which will enable future studies on the pathogenic mechanisms underlying the various phenotypic characteristics.